El sociólogo y el historiador: el rol del intelectual en la propuesta bourdieusiana - Gutiérrez, Alicia B. (El Colegio de México, 2016)
In Bourdieu's analytical perspective, the historical dimension crosses individual and collective life as objectified history in things and as incorporated history under the form of an habitus. Recognizing a historical true does not necessarily imply an eternal trap: there is a dialectic of knowledge and freedom, there is a possibility of objectifying necessity and becoming a subject. And is precisely in history where we need to search for the principle of relative independence of reason, trying to learn, reveal, and control these conditionings. In that process, the sociologist and the historian, as intellectuals, play a fundamental role. They have special tools, occupy a specific social position, and can accomplish that role, starting with the objectification of the objectifying subject.